2002
DOI: 10.1136/heart.87.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Platelet membrane glycoprotein Ibalpha gene -5T/C Kozak sequence polymorphism as an independent risk factor for the occurrence of coronary thrombosis

Abstract: Objective: To explore the potential of the GPIbα gene variable number tandem repeat (VNTR) and −5T/C Kozak polymorphisms to act as independent risk factors for myocardial infarction. Methods: 256 patients aged 33-80 years (180 caucasian, 76 Indian Asian) were recruited at cardiac catheterisation for any diagnostic indication, and divided into two groups: group A, with confirmed previous myocardial infarction evident on ECG or ventriculogram (88 patients, 79 men, 9 women) and group B, with no evidence of myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
2
18
3
2
Order By: Relevance
“…The 3 studies that found no significant association between Ϫ5C and ACSs were small and cross-sectional. [14][15][16] Perhaps more weight regarding the importance of the Ϫ5TϾC alleles should be given to the 2 studies that found an association because they were large and prospective, 12,13 similar to HERS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 studies that found no significant association between Ϫ5C and ACSs were small and cross-sectional. [14][15][16] Perhaps more weight regarding the importance of the Ϫ5TϾC alleles should be given to the 2 studies that found an association because they were large and prospective, 12,13 similar to HERS.…”
Section: Discussionmentioning
confidence: 99%
“…10 The "Kozak" polymorphism of the gene encoding GPIb␣ (GP1BA) is a TϾC substitution 5 base pairs upstream of the initiation codon that has been associated with increased platelet expression of GPIb␣ and with acute coronary syndrome (ACS) risk in some studies, [11][12][13] although other studies have found no association. [14][15][16] The gene encoding GPVI (GP6) harbors a 13254TϾC polymorphism that induces a Ser219Pro substitution; the 13254CC genotype has been associated with an increased risk of MI 17 and coronary thrombi, 18 despite being associated with less in vitro thrombogenicity on collagen. 19 Most of the genetic epidemiology studies on GP1BA and GP6 polymorphisms have been exclusively or predominantly in male patients, despite the fact that some studies suggest that genetic effects on arterial thrombosis may be greater for women than men.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study denied such an effect (Corral et al 2000). Although the jury is out in regard to the phenotypes produced by the Kozak variants, a recent study (Douglas et al 2002) found a strong association between the TT genotype and myocardial infarction (p<O.OO1). Paradoxically, this is the genotype expected from in vitro studies to confer lower expression of the receptor.…”
Section: Platelet Membrane Glycoprotein Ib-ix-vmentioning
confidence: 90%
“…ДНК выделяли из лейкоцитов крови наборами для выделения "Рапид-Генетика" ("ДНК-технология", Россия) согласно прилагаемой инструкции. Идентификацию генетических вариантов Thr145Met и T(-5)C GP Iba проводили методом ПЦР с последующим рестрикционным анализом, используя праймеры описанные ранее [12,13] и эндонуклеазы рестрикции Hin 1I и Ava II ("ThermoScientific", Литва), соответственно.…”
Section: активация тромбоцитов и цереброваскулярная патологияunclassified